2023
DOI: 10.1073/pnas.2219825120
|View full text |Cite
|
Sign up to set email alerts
|

Climate change will accelerate the high-end risk of compound drought and heatwave events

Abstract: Compound drought and heatwave (CDHW) events have garnered increased attention due to their significant impacts on agriculture, energy, water resources, and ecosystems. We quantify the projected future shifts in CDHW characteristics (such as frequency, duration, and severity) due to continued anthropogenic warming relative to the baseline recent observed period (1982 to 2019). We combine weekly drought and heatwave information for 26 climate divisions across the globe, employing historical and projected model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 65 publications
2
28
0
1
Order By: Relevance
“…In addition, our results confirm the findings in the existing literature based on GCMs (e.g. Liu et al 2021, Wu et al 2021, De Luca and Donat 2023, Tabari and Willems 2023, Tripathy et al 2023, highlighting the Mediterranean region as a hot-spot for future CHD events, which reinforce confidence in our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, our results confirm the findings in the existing literature based on GCMs (e.g. Liu et al 2021, Wu et al 2021, De Luca and Donat 2023, Tabari and Willems 2023, Tripathy et al 2023, highlighting the Mediterranean region as a hot-spot for future CHD events, which reinforce confidence in our results.…”
Section: Discussionsupporting
confidence: 92%
“…Although many studies exist analysing future projections for Europe of either droughts (Potopová et al 2018, Spinoni et al 2018, Toreti et al 2019, Hari et al 2020 or heatwaves (Molina et al 2020, Lin et al 2022, studies analysing future CHD events mainly focus on either the global scale (e.g. Liu et al 2021, Wu et al 2021, De Luca and Donat 2023, Tabari and Willems 2023, Tripathy et al 2023 or specific regions only, such as central Europe (Sedlmeier et al 2018, Zscheischler andFischer 2020). For instance, Wu et al (2021), Liu et al (2021), Tripathy et al (2023), Tabari and Willems (2023) and De Luca and Donat (2023) found that central Europe and the Mediterranean are amongst the regions showing stronger increase in frequency and intensity of CHD events through the late 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for the Balkans and Scandinavia the evaluated RPs are relatively less, with their median RPs are ∼75 and ∼50 years, respectively. As climate change continues to impact the planet, the RPs of CDHW events are becoming more likely to occur in the future (Tripathy et al., 2023; Zhang et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…When these two events occur together (i.e., Compound Drought and Heatwaves (CDHW)), they can lead to even more severe consequences (Geirinhas et al., 2021; Hao et al., 2022; Libonati et al., 2022; Mukherjee & Mishra, 2021). In Europe, CDHW events have caused significant economic losses, affecting various sectors such as agriculture, health, energy, and tourism (Brás et al., 2021; Mazdiyasni & AghaKouchak, 2015; Tripathy et al., 2023; Yin et al., 2022; Zhou et al., 2019b). For instance, the 2003 heatwave and drought in Europe resulted in a total loss of €15 billion (European Environment Agency, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation